1997
DOI: 10.1073/pnas.94.25.13792
|View full text |Cite
|
Sign up to set email alerts
|

Multiple pathways for SOS-induced mutagenesis in Escherichia coli : An overexpression of dinB / dinP results in strongly enhancing mutagenesis in the absence of any exogenous treatment to damage DNA

Abstract: ABSTRACTdinP is an Escherichia coli gene recently identified at 5.5 min of the genetic map, whose product shows a similarity in amino acid sequence to the E. coli UmuC protein involved in DNA damage-induced mutagenesis. In this paper we show that the gene is identical to dinB, an SOS gene previously localized near the lac locus at 8 min, the function of which was shown to be required for mutagenesis of nonirradiated phage infecting UV-preirradiated bacterial cells (termed UTM for untargeted mutagenesis). A new… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
303
2
3

Year Published

1999
1999
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 319 publications
(326 citation statements)
references
References 58 publications
(65 reference statements)
18
303
2
3
Order By: Relevance
“…Further analyses showed no strain difference in the types of mutational events at the repeat allele. This result was surprising to us, as Pol IV was shown to create -1 frameshifts in homopolymeric G 6 runs [22]. The difference between our study and the previous study [22] could be due to sequence context effects (lac gene vs. HSV-tk gene) or the length of the repetitive target (6 vs. 10 nucleotides).…”
Section: Pol IV and Microsatellite Mutagenesiscontrasting
confidence: 88%
See 3 more Smart Citations
“…Further analyses showed no strain difference in the types of mutational events at the repeat allele. This result was surprising to us, as Pol IV was shown to create -1 frameshifts in homopolymeric G 6 runs [22]. The difference between our study and the previous study [22] could be due to sequence context effects (lac gene vs. HSV-tk gene) or the length of the repetitive target (6 vs. 10 nucleotides).…”
Section: Pol IV and Microsatellite Mutagenesiscontrasting
confidence: 88%
“…coli polymerase IV is a distributive polymerase that lacks a 3'to 5' exonuclease (proofreading) activity and is prone to elongation of misaligned primer/template structures [20]. The overespression of the polymerase causes -1 frameshifts in polypurine runs of G in undamaged DNA [22]. When looking at spontaneous mutagenesis, previous studies have shown a statistically significant decrease in the number of frameshift and base substitution events in the absence of dinB [23,24,32] while overexpression of the dinB gene results in a significant increase in the mutation frequency [21,22].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Spontaneous mutagenesis induced by overexpression of DinB exhibits a strong preference for -1 frameshift mutations, but also a substantial increase in certain base substitution mutations at purines. 16 Moreover, treatment with 4-NQO dramatically increases the frequency of -1 frameshift mutations observed. Despite the relative ambiguity of these phenomena, they laid the foundation, particularly in concert with the known mutagenic phenotypes of the dinB homolog umuC, for a view of dinB as an agent of mutation.…”
Section: Untargeted Spontaneous and Induced Mutagenesismentioning
confidence: 99%